An examination of response variability in children with autism and the relationship to restricted repetitive behavior subtypes. (March 2015) - Murray, Clodagh; Healy, Olive
Highlights: We examined response variability in children with autism and its relationship to restricted repetitive behaviors. Response variability was compared for children with autism and typically developing children. Significantly lower variability was shown for the autism group. Variability was significantly negatively correlated with total RBS-R scores and with the stereotypy subscale and the Self-Injurious behavior subscale. Abstract: The current study investigated response variability in children with autism and its relationship to restricted repetitive behaviors, one of the core symptoms of the disorder. The "Penny-Hiding Game" (Baron-Cohen, 1992 ) was used as a measure of response variability. Variability was compared for children with autism ( n = 65) and typically developing children ( n = 65) and patterns of response variability were categorized from least variable to most variable for both groups. For the participants with a diagnosis of autism, these patterns were examined relative to their scores on the Repetitive Behavior Scale-Revised (RBS-R; Bodfish, Symons, & Lewis, 1999). Results showed that children with autism demonstrated significantly lower variability in their responding in the "Penny-Hiding Game" than their typically developing peers. Variability was significantly negatively correlated with total RBS-R scores and with the Stereotypy subscale and the self-injurious behavior subscale, indicating that lower variability in responding was related to higher rates of these types of restricted and repetitive behaviors. No significant correlations were observed between variability and the Compulsion subscale, the Ritualistic/Sameness behaviors subscale or the Restricted Interests subscale.